Los tres cerdos Nacho, Tito, e Miguel - Salinas-Norman, Bobbi (Alameda, CA: Pinata Publications, 1997)
Summary: This version of The Three Pigs takes place in the Southwest. Miguel, the cleverest of the pigs, sees through the wolf's artificially sugared tricks and ultimately destroys the wolf's power to deceive others.
Includes glossary.
For children 3-103.
Para ninos de 3 a 103 anos de edad.
Text in Spanish and English.
Keywords: Swine -- Juvenile fiction; Wolves -- Juvenile fiction; Children's stories, American -- translation into Spanish; Bilingual materials -- Spanish and English; Fables -- Juvenile fiction